Human BDCA2+CD123+CD56+ dendritic cells (DCs) related to blastic plasmacytoid dendritic cell neoplasm represent a unique myeloid DC subset. Issue 4 (18th March 2015) - Yu, Haisheng; Zhang, Peng; Yin, Xiangyun; Yin, Zhao; Shi, Quanxing; Cui, Ya; Liu, Guanyuan; Wang, Shouli; Piccaluga, Pier Paolo; Jiang, Taijiao; Zhang, Liguo
Abstract: Dendritic cells (DCs) comprise two functionally distinct subsets: plasmacytoid DCs (pDCs) and myeloid DCs (mDCs). pDCs are specialized in rapid and massive secretion of type I interferon (IFN-I) in response to nucleic acids through Toll like receptor (TLR)-7 or TLR-9. In this report, we characterized a CD56 + DC population that express typical pDC markers including CD123 and BDCA2 but produce much less IFN-I comparing with pDCs. In addition, CD56 + DCs cluster together with mDCs but not pDCs by genome-wide transcriptional profiling. Accordingly, CD56 + DCs functionally resemble mDCs by producing IL-12 upon TLR4 stimulation and priming naïve T cells without prior activation. These data suggest that the CD56 + DCs represent a novel mDC subset mixed with some pDC features. A CD4 + CD56 + hematological malignancy was classified as blastic plasmacytoid dendritic cell neoplasm (BPDCN) due to its expression of characteristic molecules of pDCs. However, we demonstrated that BPDCN is closer to CD56 + DCs than pDCs by global gene-expression profiling. Thus, we propose that the CD4 + CD56 + neoplasm may be a tumor counterpart of CD56 + mDCs but not pDCs.